2021
DOI: 10.7717/peerj.11102
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of miR-381-3p and miR-23b-3p in skeletal muscle could be a possible estimator of early post-mortem interval in rats

Abstract: Background The post-mortem interval (PMI) is the time elapsed since the dead of an individual until the body is found, which is relevant for forensic purposes. The miRNAs regulate the expression of some genes; and due to their small size, they can better support degradation, which makes them suitable for forensic analysis. In the present work, we evaluated the gene expression of miR-381-3p, miR-23b-3p, and miR-144-3p in skeletal muscle in a murine model at the early PMI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The expression of miR-381-3p was the highest in IUGR pig skeletal muscle, accounting for 21.17% (normal: 9.86%), while the expression of miR-206 in normal pig skeletal muscle was the highest, accounting for 15.45% (IUGR: 10.13%). Previous studies have reported that miR-381-3p may be involved in the autolysis of skeletal muscle in the early stage of death [ 38 ]; these results suggest that miR-381 may play an important role in regulating skeletal muscle homeostasis in IUGR animals.…”
Section: Discussionmentioning
confidence: 86%
“…The expression of miR-381-3p was the highest in IUGR pig skeletal muscle, accounting for 21.17% (normal: 9.86%), while the expression of miR-206 in normal pig skeletal muscle was the highest, accounting for 15.45% (IUGR: 10.13%). Previous studies have reported that miR-381-3p may be involved in the autolysis of skeletal muscle in the early stage of death [ 38 ]; these results suggest that miR-381 may play an important role in regulating skeletal muscle homeostasis in IUGR animals.…”
Section: Discussionmentioning
confidence: 86%
“…Although it is expected that the expression of some of these miRNAs decays as the PMI increases, there are miRNAs whose expression increases at PMI, such as MiR195 and MiR122 ( Wang et al, 2013a ). In fact, in our lab we found an increase in the expression of miR-381-3p in rats’ skeletal muscle at the 24 h of PMI ( Martínez-Rivera et al, 2021 ). This suggests that just as with some mRNAs, there is an upregulation of miRNAs which are needed for the body decomposition process.…”
Section: Introductionmentioning
confidence: 73%
“…A total of five rat skeletal muscle samples were obtained from a postmortem interval rat model which was previously established in our laboratory ( Martínez-Rivera et al, 2021 ). In brief, nine adult male Wistar rats were selected for the study; all with an average weight of 200 gr.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations